Miracle or mirage. What role can trade policies play in tackling global trade imbalances? - Flaig, Dorothee; Haugh, David; Kowalski, Przemyslaw; Rouzet, Dorothée; van Tongeren, Frank (Paris, 2018)
"Global trade imbalances narrowed in the aftermath of the global financial crisis. They have remained at a lower level but are still of concern to policy makers because of the risks they pose to individual economies, as well as globally. However, the ultimate causes of these imbalances are not fully clear. Current account positions reflect the gap between national saving and investment, which are in turn affected by policy distortions, including in trade policy. Simulations of the OECD’s METRO model show liberalisation of existing trade distortions would modestly narrow aggregate trade imbalances in the medium term for some countries. Reducing tariffs, non-tariff measures and the combined market access and productivity-enhancing effects of pro-competitive measures in services all have some rebalancing potential. Liberalisation would also offer economically significant income gains for all countries. By contrast, narrowing trade imbalances using trade restrictions would come at disproportionately high economic costs for all countries."